The Western Alpine arc: a review and new kinematic model - Brunsmann, Quentin; Rosenberg, Claudio Luca; Bellahsen, Nicolas (Comptes Rendus. Géoscience)
The arcuate shape of the Western Alps is commonly interpreted to result from collisional, NW-ward indentation of the Adriatic indenter. The radial pattern (${≈ }$180°) of collisional transport directions is difficult to explain, especially in the southern WNW–ESE to E–W striking arc segments. A mid-Cenozoic change, from NW- to W-directed indentation is often proposed, but poorly constrained. Based on a critical review of conceptual models for the formation of the Western Alpine arc and associated geodynamic processes, we conclude that an arcuate structure already exists before the onset of collision. NW-ward indentation of the Adriatic indenter amplifies this arc structure by oroclinal bending, but the E–W to ESE–WNW striking, southernmost segments of the Alpine arc mainly result from distinct geodynamic processes, other than Alpine convergence in the strict sense. The southernmost External Zone is mainly inherited from the Pyrenean orogeny and was weakly reactivated in the Miocene, probably accommodating very small parts of Africa–Europe convergence since Late Miocene times. In the Internal Zone, the E–W strike of the Ligurian Alps is probably associated with 50° counterclockwise rotation of the northern Apennines.